Kebijakan Amerika Serikat terhadap Perusahaan Teknologi Digital Tiongkok - Andre Eka Saputra (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
This thesis examines United States policy toward Chinese technology companies in the context of global technological competition. The rapid growth of companies such as Huawei, ZTE, and TikTok has positioned China as a significant actor in digital infrastructure, data-driven platforms, and the technology supply chain. This development has generated a political and security response from the United States through restrictive policies justified under the discourse of national security. This study uses a qualitative approach with descriptive-analytical methods and employs securitization theory as the primary analytical framework. Data were collected from official US government documents, congressional reports, public statements, institutional reports, academic literature, and credible news sources. The findings in this thesis indicate that US policy toward Chinese technology companies is not merely economic or trade policy, but rather the result of a securitization process. Chinese technology companies are perceived as a threat to US national security, particularly related to data security, digital infrastructure, the technology supply chain, and technological sovereignty. This construction of threat is used to legitimize restrictive policies such as the Entity List, export controls, investment restrictions, digital application restrictions, and data transaction surveillance. Therefore, US policy toward Chinese technology companies can be understood as extraordinary measures resulting from technology securitization
Approved by Teddy
Keywords: National Security; Non-Traditional Security